Oxidation – Antioxidation - Suarez Cunza, Silvia (2015)
For aerobic organisms it is essential atmospheric oxygen use. Though, it is also known that about 2-5% of that oxygen is reduced to form free radicals (ROS) such as superoxide, hydroxyl radical and hydrogen peroxide molecule in addition to organic peroxides produced by propagation reactions that can damage cellular biomolecules and starting at the best apoptosis and necrosis. As part of our evolution and  adaptation to this gas toxicity we have developed a complex antioxidant defense system with endogenous components (superoxide dismutase-SOD, catalase, glutathione peroxidase, glutathione, uric acid, bilirubin, lipoic acid) and exogenous (Vitamins A, C and E, as well as polyphenols) that are included in our daily diet. This paradox of oxygen throughout life leads to a state of oxidative stress and contributes to the process of senescence, however not uniform for all our body systems. In human life the female reproductive system ages more rapidly with characteristic decline in estrogen production that in addition to its classical hormonal function has also shown direct antioxidant capacity and participates in intracellular signals activation for redox homeostasis.